Everolimus downregulates estrogen receptor and induces autophagy in aromatase inhibitor-resistant breast cancer cells. Issue 1 (December 2016) - Lui, Asona; New, Jacob; Ogony, Joshua; Thomas, Sufi; Lewis-Wambi, Joan
Abstract Background mTOR inhibition of aromatase inhibitor (AI)-resistant breast cancer is currently under evaluation in the clinic. Everolimus/RAD001 (Afinitor®) has had limited efficacy as a solo agent but is projected to become part of combination therapy for AI-resistant breast cancer. This study was conducted to investigate the anti-proliferative and resistance mechanisms of everolimus in AI-resistant breast cancer cells. Methods In this study we utilized two AI-resistant breast cancer cell lines, MCF-7:5C and MCF-7:2A, which were clonally derived from estrogen receptor positive (ER+) MCF-7 breast cancer cells following long-term estrogen deprivation. Cell viability assay, colony formation assay, cell cycle analysis and soft agar anchorage-independent growth assay were used to determine the efficacy of everolimus in inhibiting the proliferation and tumor forming potential of MCF-7, MCF-7:5C, MCF-7:2A and MCF10A cells. Confocal microscopy and transmission electron microscopy were used to evaluate LC3-II production and autophagosome formation, while ERE-luciferase reporter, Western blot, and RT-PCR analyses were used to assess ER expression and transcriptional activity. Results Everolimus inhibited the proliferation of MCF-7:5C and MCF-7:2A cells with relatively equal efficiency to parental MCF-7 breast cancer cells. The inhibitory effect of everolimus was due to G1 arrest as a result of downregulation of cyclin D1 and p21. Everolimus also dramatically reduced estrogen receptor (ER) expression (mRNA and protein) and transcriptional activity in addition to the ER chaperone, heat shock protein 90 protein (HSP90). Everolimus restored 4-hydroxy-tamoxifen (4OHT) sensitivity in MCF-7:5C cells and enhanced 4OHT sensitivity in MCF-7 and MCF-7:2A cells. Notably, we found that autophagy is one method of everolimus insensitivity in MCF-7 breast cancer cell lines. Conclusion This study provides additional insight into the mechanism(s) of action of everolimus that can be used to enhance the utility of mTOR inhibitors as part of combination therapy for AI-resistant breast cancer.